Ageing of lithium-ion battery modules with dissipative balancing compared with single-cell ageing. (May 2016) - Campestrini, Christian; Keil, Peter; Schuster, Simon F.; Jossen, Andreas
Abstract : Highlights: Ageing of lithium-ion battery modules compared with single-cell ageing. Construction of modules allows investigation of battery parameters' inhomogeneity. Dissipative balancing behaviour over the modules' lifetime is investigated. Modules do not age worse than single cells due to temperature effects. Abstract: In contrast to numerous published lithium-ion cell ageing investigations, reports regarding the ageing behaviour of entire modules are scarce. This study compares the ageing behaviour of lithium-ion battery modules with the one of single cells. A capacity-based cell matching procedure is performed to minimise the capacity spread among the blocks of constructed modules. So, the newly introduced state of inhomogeneity (regarding capacity and resistance) is reduced up to 10%, but, however, also observed to increase rather linearly over the modules' lifetime. The balancing behaviour of the battery management system stays unaffected of this increased inhomogeneity. To gain a deeper insight into the ageing behaviour of multi-cell batteries, the modules are disassembled and analysed in terms of local temperature distribution and cell-to-cell variation. After 1200 equivalent full cycles, the modules show an overall module capacity loss which is about 12%. Thereby, the module ageing study reveals a capacity fade which is even approximately 2% lower compared with the one of single cells. The state of inhomogeneity for capacity of high quality lithium-ion cells after 1200 equivalent full cycles is still smaller than 1%.